The Elusive Empire : Kazan and the Creation of Russia, 1552-1671 (University of Wisconsin Press, 2012)
In 1552, Muscovite Russia conquered the city of Kazan on the Volga River. It was the first Orthodox Christian victory against Islam since the fall of Constantinople, a turning point that, over the next four years, would complete Moscow's control over the river. This conquest provided a direct trade route with the Middle East and would transform Muscovy into a global power. As Matthew Romaniello shows, however, learning to manage the conquered lands and peoples would take decades. Russia did not succeed in empire-building because of its strength, leadership, or even the weakness of its neighbors, Romaniello contends; it succeeded by managing its failures. Faced with the difficulty of assimilating culturally and religiously alien peoples across thousands of miles, the Russian state was forced to compromise in ways that, for a time, permitted local elites of diverse backgrounds to share in governance and to preserve a measure of autonomy. Conscious manipulation of political and religious language proved more vital than sheer military might. For early modern Russia, empire was still elusive-an aspiration to political, economic, and military control challenged by continuing resistance, mismanagement, and tenuous influence over vast expanses of territory.
Includes bibliographical references and index.
Keywords: Soviet Union -- Foreign relations; Kazanskoe khanstvo -- Foreign relations -- Soviet Union; Russia -- History -- Period of Consolidation, 1462-1605.; Russia -- History -- Time of Troubles, 1598-1613.; Orthodox Eastern Church -- Russia -- History; Religion and politics -- Russia -- History; HISTORY / Europe / Eastern; HISTORY / Europe / Former Soviet Republics; HISTORY / Europe / Russia & the Former Soviet Union; Electronic books